Guerrilla marketing : - Levinson, Jay Conrad (Houghton Mifflin, 2007)
When Guerrilla Marketing was first published in 1983, Jay Levinson revolutionized marketing strategies for the small-business owner with his take-no-prisoners approach to finding clients. Based on hundreds of solid ideas that really work, Levinson’s philosophy has given birth to a new way of learning about market share and how to gain it. In this completely updated and expanded fourth edition, Levinson offers a new arsenal of weaponry for small-business success including.